The Effect of CSR Disclosure On Firm Risk In Mining Companies Listed On IDX - Thanaya, Sayu Aryantini; Widanaputra, A.A.G.P. (E-Jurnal Akuntansi, 2019)
This research aims to obtain empirical evidence on the effect of corporate social responsibility disclosure on firm risk. This research was conducted on mining companies listed on Indonesia Stock Exchange in 2015-2017. The sample determination method is purposive sampling, with 109 observations. The data analysis technique used is simple linear regression analysis. Based on the research results, it is known that corporate social responsibility disclosure has a negative effect on firm risk. This means that the more CSR disclosure of a company, the lower the firm risk. The implications of the research results supports the signaling theory, stakeholder theory, and legitimacy theory, where risk management efforts are done by sending positive signals through the disclosure of CSR information, to gain the support and trust from the company's stakeholders, and increase the organization's legitimacy. On the other hand, this research provides additional information for all company stakeholders in making decisions. Keywords : CSR Disclosure; Firm Risk; Mining.